2009
DOI: 10.1016/j.neuro.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of dopaminochrome in the mesencephalic cell line, MN9D, is dependent upon oxidative stress

Abstract: Parkinson disease is a specific form of neurodegeneration characterized by a loss of nigra-striatal dopaminergic neurons in the midbrain of humans. The disease is also characterized by an increase in oxidative stress and a loss of glutathione in the midbrain region. A potential link between all these factors is the oxidation of dopamine to dopaminochrome (DAC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…2). Aminochrome has been shown to be toxic to murine mesencephalic MN9D cells at concentrations as low as 50 μM (Linsenbardt et al, 2009). In the mesencephalic cell line, MN9, aminochrome induces caspase-independent apoptosis (Linsenbardt et al, 2012).…”
Section: Spontaneous Oxidation Of Catecholaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Aminochrome has been shown to be toxic to murine mesencephalic MN9D cells at concentrations as low as 50 μM (Linsenbardt et al, 2009). In the mesencephalic cell line, MN9, aminochrome induces caspase-independent apoptosis (Linsenbardt et al, 2012).…”
Section: Spontaneous Oxidation Of Catecholaminesmentioning
confidence: 99%
“…Anti-oxidant pre-treatment of animals or cells can attenuate or prevent neurotoxic effects of MPTP (Blanchet et al, 2008), MPP+ (Wu et al, 1994), levodopa (Lai & Yu, 1997; Peritore et al, 2012), DA (Lai & Yu, 1997; Wu & Johnson, 2011), and aminochrome (Linsenbardt et al, 2009). Metal ions, especially ions of iron, have long been suspected to participate in the pathogenetic process (Sofic et al, 1988; Ben-Shachar & Youdim, 1993; Youdim et al, 1993; Berg et al, 2001; Gotz et al, 2004; Jomova et al, 2010).…”
Section: Therapeutic Implications Of Catecholamine Autotoxicitymentioning
confidence: 99%
“…A potential explanation for the less-than-hoped-for results of MAO inhibition is secondary buildup of cytoplasmic DA and, consequently, augmented spontaneous oxidation of DA to form DA-quinone, which might offset beneficial effects of decreased DOPAL production. DA-quinone is toxic via spontaneous conversion to dopaminochrome (Linsenbardt et al, 2009;Aguirre et al, 2012) and reactivity with glutathione or cysteine to form 5-S-cysteinyl-dopamine (Cys-DA) (Montine et al, 1997;Spencer et al, 2002). Cys-DA provides a biomarker of DA auto-oxidation (Fornstedt et al, 1986;Carlsson and Fornstedt, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…DA oxidation produces dopaminochrome (DAC) [10, 21, 42, 50, 56], a component of neuromelanin, the substance that pigments SNpc neurons [17, 60]. We have previously reported that DAC is cytotoxic to mesencephalic cells in an oxidative stress-dependent manner [35, 36]. …”
Section: Introductionmentioning
confidence: 99%